5-tert-Butyl-2-[5-(5-tert-butyl-1,3-benzoxazol-2-yl)-2-thienyl]-1,3-benzoxazole - Fang-Fang Jian; Lin-Tong Wang; Yu-Feng Li (Acta Crystallographica Section E, 2008)
The title compound, C26H26N2O2S, was prepared by the reaction of thiophene-2,5-dicarboxylic acid and 2-amino-4-tert-butylphenol. One of the tert-butyl groups is disordered over two conformations, with occupancies of 0.539 (1) and 0.461 (2). The two 1,3-benzoxazole rings are almost planar, with dihedral angles of 0.83 (18) and 1.64 (17)° between the five- and six-membered rings. The thiophene ring makes dihedral angles of 21.54 (19) and 4.49 (18)° with the planes of the five-membered oxazole rings. The crystal packing is controlled by π–π stacking interactions involving the thiophene and benzene rings, with a centroid–centroid distance of 3.748 (2) Å.